Reply to comment on 'Quantization rules for bound states in quantum wells' - Gomes, MAF; Adhikari, S. K. (Iop Publishing Ltd, 2000)
In this reply to the comment on 'Quantization rules for bound states in quantum wells' we point out some interesting differences between the supersymmetric Wentzel-Kramers-Brillouin (WKB) quantization rule and a matrix generalization of usual WKB (mWKB) and Bohr-Sommerfeld (mBS) quantization rules suggested by us. There are certain advantages in each of the supersymmetric WKB (SWKB), mWKB and mBS quantization rules. Depending on the quantum well, one of these could be more useful than the other and it is premature to claim unconditional superiority of SWKB over mWKB and mBS quantization rules.